PWE-005 Initial experience of spyglass per-oral cholangioscopy in a UK centre. (23rd September 2015) - Aljabiri, M; Lerman, A; Kalaitzakis, E; Winstanley, A; Noveli, M; Pereira, S; Hatfield, A; Webster, G
Abstract : Introduction: Endoscopic retrograde cholangiopancreatography (ERCP) and biliary brush cytology fail to definitively diagnose the cause of biliary strictures and other intraductal lesions in the majority of cases. Recent advances in cholangioscopy allow direct mucosal visualisation and directed tissue sampling, which may improve diagnostic yield in these cases. Aim: To evaluate initial experience of Spyglass cholangioscopy in our tertiary centre. Methods: We retrospectively analysed patient demographics, indications for use, technical success, complications, and diagnostic yield in all cases of Spyglass cholangioscopy performed over the first year of use. Results: Cholangioscopy was performed in 30 patients (21M:9F) in 2008–9, representing 30/723 (4%) of total ERCPs. 22 (73%) patients had undergone ERCP prior to referral. Indications for cholangioscopy included: indeterminate strictures (n=14 (47%)); intraductal mass lesion / filling defects (n=15 (50%)); suspected intraductal papillary mucinous neoplasm (n=1 (3%)). Cholangioscope insertion and mucosal visualisation was achieved in 97% (cholangioscope insertion was failed technically in one patient). One patient (3%) developed mild pancreatitis, and three (10%) developed pain during procedure due to water flushing above strictures, but without subsequent complication. Directed Spybite biopsies were taken in 12/30 (40%) of cases, with sufficient tissue for histological analysis in 10/12 (83%). A definitive histological diagnoses was reached in 8/10 (80%) with adequate tissue witha 67% sensitivity, and included: intraductal carcinoid (n=1), poorly differentiated adenocarcinoma (n=2), low grade dysplasia of the duct (n=2), IgG4 associated cholangitis (IAC) (n=2), intrahepatic papillary mucinous tumour (n=1). In conjunction with other diagnostic modalities (ERCP, CT, MRCP, EUS, percutaneous biopsy), the following final diagnoses were made: bile duct tumour (various types) (n=10), strictures (n=12) bnign secondary to CBD stone disease out of these 12 patients primary sclerosing cholangitis (n=5), common bile duct stones (n=3) these referrals were for therapy, IAC (n=1), pancreatic IPMN (n=1), common bile duct stones (n=1), peridochal varices (n=1), Liver mets resulting in compression of CBD (n=1). Conclusion: To date, Spyglass cholangioscopy has been used in our practice to "trouble shoot", where standard diagnostics have failed to achieve diagnosis. In small patient cohort safety profile appears good. Despite small tissue samples, directed biopsies have allowed definitive histological diagnoses to be made, which have significantly changed patient management. Further studies will better define role of cholangioscopy in diagnostic algorithm.